Immediate Effects of Kinesio-taping and Joint Mobilisation on Shoulder in Over-head Athletes with Glenohumeral Internal Rotation Deficit - Amrinder Singh; Yogini Makhijani; Monika Sharma; Shweta Shenoy; Jaspal Sandhu (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2023)
The purpose of this study was to compare efficacy of kinesio taping (K-taping) and joint mobilization as immediate interventions for treating athletes with glenohumeral internal rotation deficit (GIRD). Thirty-two asymptomatic players were recruited from basketball, volleyball and handball who had a loss of shoulder internal rotation range of motion (IR ROM) of 10 degrees or more on their dominant compared to non-dominant side. They were randomly assigned to 1 of 2 groups: K-taping (n  =  16) or joint mobilization (n  =  16). Participants in taping group were treated with K-tape for inhibition of external rotators of shoulder and participants in joint mobilization group were treated with grade four Maitland's mobilization technique for increasing glenohumeral internal rotation. Shoulder internal and external ROM were measured before and after the intervention with a universal goniometer. Both the methods produced significant improvement in IR ROM. The unpaired t-test showed significant change in IR ROM within both the groups (p = 0.003). No significant change was found on comparing both the groups (p = 0.373). There were no significant differences between results of the three sports (p = 0.592). K-taping and joint mobilization both are equally effective in improving the IR ROM in over-head players with GIRD.